Acute Shift in Glutamate Concentrations Following Experimentally Induced Panic with Cholecystokinin Tetrapeptide—A 3T-MRS Study in Healthy Subjects - Zwanzger, Peter; Zavorotnyy, Maxim; Gencheva, Elena; Diemer, Julia; Kugel, Harald; Heindel, Walter; Ruland, Tillmann; Ohrmann, Patricia; Arolt, Volker; Domschke, Katharina; Pfleiderer, Bettina (Neuropsychopharmacology (New York, N.Y.), 2013)
According to preclinical studies, glutamate has been implicated in the pathogenesis of anxiety. In order to elucidate the role of glutamate in anxiety and panic in humans, brain glutamate+glutamine (Glx) levels were measured during cholecystokinin-tetrapeptide (CCK-4)-induced panic using magnetic resonance spectroscopy (MRS). Eighteen healthy subjects underwent a CCK-4 challenge. MR spectra were obtained from the anterior cingulate cortex (ACC) using a single voxel point-resolved spectroscopy method and analyzed using LCModel. A combined fitting of Glx was performed. Panic was assessed using the Acute Panic Inventory (API) and Panic Symptom Scale (PSS) scores. Moreover, hypothalamic-pituitary-adrenal axis stimulation was monitored throughout the challenge. There was a significant panic response following CCK-4 as revealed by a marked increase in both the panic scores (API: F(1,17)=149.41; p<0.0001; PSS: F(1,17)=88.03; p<0.0001) and heart rate (HR: F(1,17)=72.79; p<0.0001). MRS measures showed a significant increase of brain Glx/creatine (Glx/Cr) levels peaking at 2-10 min after challenge (F(1,17)=15.94; p=0.001). There was also a significant increase in CCK-4-related cortisol release (F(6,11)=8.68; p=0.002). Finally, significant positive correlations were found between baseline Glx/Cr and both APImax (r=0.598; p=0.009) and maximum heart rate (HR(max)) during challenge (r=0.519; p=0.027). Our results suggest that CCK-4-induced panic is accompanied by a significant glutamate increase in the bilateral ACC. The results add to the hypothesis of a disturbance of the inhibitory-excitatory equilibrium and suggest that apart from static alterations rapid and dynamic neurochemical changes might also be relevant for the neural control of panic attacks.